Studi Etnobiologi dalam Makanan Tradisional Garang Asem di Desa Dimoro Kabupaten Grobogan Jawa Tengah - Aulia Septiani; Marina Silalahi (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
Traditional food is local wisdom passed down from generation to generation, including ayam garang asem (a type of chicken curry with a very prominent sour taste). The aim of this research is the diversity of plants used to make garang asem and the process of making it. The research method uses an ethnobotanical approach through surveys and semi-structured interviews. Data was analyzed qualitatively. Ayam garang asem is one of the traditional Javanese ethnic foods in Gumuro village with the main flavors being spicy (garang) and tamarind (asem). The taste of tamarind chicken comes from the plants used, namely spicy (chili) and tamarind (starfruit). It was found that 11 species (12 local name) belonging 8 families and 10 genera of plants were used as ingredients to prepare tamarind chicken. Plants are dominated by the Solanaceae family (4 species), followed by Liliaceae (2 species), the rest are one species for each family. The use of starfruit and bay leaves has great potential to be developed as cooking spices because they have antimicrobial bioactivity so they have great potential to be developed as natural food preservatives.